Effects of oxygen transfer coefficient on dihydroxyacetone production from crude glycerol - Zheng,Xiao-juan (2016)
Abstract The principal objective of this study was to evaluate the kinetics of dihydroxyacetone production by Gluconobacter frateurii CGMCC 5397 under different oxygen volumetric mass transfer coefficient (kLa) conditions in submerged bioreactors using biodiesel-derived crude glycerol as the carbon source. kLa is a key fermentation parameter for the production of dihydroxyacetone. Cultivations were conducted in baffled- and unbaffled-flask cultures (the kLa values were 24.32 h−1 and 52.05 h−1, respectively) and fed-batch cultures (the kLa values were held at 18.21 h−1, 46.03 h−1, and 82.14 h−1) to achieve high dihydroxyacetone concentration and productivity. The results showed that a high kLa could dramatically increase dihydroxyacetone concentrations and productivities. The baffled-flask culture (with a kLa of 52.05 h−1) favored glycerol utilization and dihydroxyacetone production, and a dihydroxyacetone concentration as high as 131.16 g/L was achieved. When the kLa was set to 82.14 h−1 in the fed-batch culture, the dihydroxyacetone concentration, productivity and yield were 175.44 g/L, 7.96 g/L/h and 0.89 g/g, respectively, all of which were significantly higher than those in previous studies and will benefit dihydroxyacetone industrial production.